ANALISIS PEMANFAATAN SUMBER BELAJAR DALAM MENUNJANG PROSES PEMBELAJARAN EKONOMI DI SMA NEGERI 01 BONTI - Arun, Arun; Aminuyati, Aminuyati; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is the use of learning resources in supporting the learning process in SMA Negeri 01 Bonti, Sanggau Regency. It is a qualitative research with a descriptive approach. The data collection tools used in this research are interview guidelines, observation checklist and triangulation. The data analysis in this thesis is presented in a descriptive qualitative technique using informants from 1 subject economics teacher, 1 computer laboratory manager and 1 library manager. The results of this study indicate that from these findings, it is said that learning resources available at the SMA Negeri 01 Bonti are sufficient enough that only the need for additional equipment is necessary. Utilization of learning resources in supporting the process of economic learning in SMA Negeri Bonti 01 is done in various ways, one of the examples is the economics’ teacher trying to utilize the learning resources available in the school by providing students with material and then told to look for these materials from various learning sources ranging from textbooks and internet, hence learning is not focused on one learning source. Then utilizing a computer laboratory to practice according to the needs and the material being taught Keywords: learning resources, economic learning process